Theranostic siRNA loaded mesoporous silica nanoplatforms: A game changer in gene therapy for cancer treatment - Anwesha Kanungo; Nigam Sekhar Tripathy; Liza Sahoo; Sarbari Acharya; Fahima Dilnawaz (Elsevier, 2024)
Growing interest has been seen in non-pathogenic, safe, and effective gene therapy delivery systems. There are many nucleic acid therapies that have been studied to alter the expression of DNA or RNA, such as mRNA, siRNA, antisense DNA, and microRNA (miRNA), of which siRNA has been shown to be useful in blocking specific genes. The development of an efficient nucleic acid delivery method is crucial for molecular diagnostic and therapeutic systems. Mesoporous silica nanoparticles (MSNs) with high porosity, good textural qualities, and biocompatibility have been studied for use in drug delivery systems. They are being utilized more and more in combination therapy, gene silencing, and other biological applications, especially in cancer nanomedicine. MSNs offer efficient drug loading and controlled release, and additions can change their characteristics. They are widely employed in target medication delivery, biosensing, cellular uptake, and diagnostics in the biomedical field. Additionally, they have been connected to theranostic drugs for cancer treatment. This review highlights the current state of knowledge of MSNs and their specialized applications as theranostic agents for cancer management.